Power-to-fuels via solid-oxide electrolyzer: Operating window and techno-economics. (August 2019) - Wang, Ligang; Chen, Ming; Küngas, Rainer; Lin, Tzu-En; Diethelm, Stefan; Maréchal, François; Van herle, Jan
Abstract: Power-to-fuel systems via solid-oxide electrolysis are promising for storing excess renewable electricity by efficient electrolysis of steam (or co-electrolysis of steam and CO2 ) into hydrogen (or syngas), which can be further converted into synthetic fuels with plant-wise thermal integration. Electrolysis stack performance and durability determine the system design, performance, and long-term operating strategy; thus, solid-oxide electrolyzer based power-to-fuels were investigated from the stack to system levels. At the stack level, the data from a 6000-h stack testing under laboratory isothermal conditions were used to calibrate a quasi-2D model, which enables to predict practical, isothermal stack performance with reasonable accuracy. Feasible stack operating windows meeting various design specifications (e.g., specific syngas composition) were further generated to support the selection of operating points. At the system level, with the chosen similar stack operating points, various power-to-fuel systems, including power-to-hydrogen, power-to-methane, power-to-methanol (dimethyl ether) and power-to-gasoline, were compared techno-economically considering system-level heat integration. Several operating strategies of the stack were compared to address the increase in stack temperature due to degradation. The modeling results show that the system efficiency for producing H2, methane, methanol/dimethyl ether and gasoline decreases sequentially from 94% (power-to-H2 ) to 64% (power-to-gasoline), based on a higher heating value. Co-electrolysis, which allows better heat integration, can improve the efficiency of the systems with less exothermic fuel-synthesis processes (e.g., methanol/dimethyl ether) but offers limited advantages for power-to-methane and power-to-gasoline systems. In a likely future scenario, where the growing amount of electricity from renewable sources results in increasing periods of a negative electricity price, solid oxide electrolyser based power-to-fuel systems are highly suitable for levelling the price fluctuations in an economic way. Highlights: The stack operating windows can be enlarged by co-electrolysis and increased current densities. System efficiency of power-to-hydrogen, -methane, -methanol and -gasoline decreases from 94% to 64%. Co-electrolysis is advantageous for power-to-methanol but not for power-to-methane and -gasoline. The investigated power-to-fuel systems are suitable for economically levelling electricity-price fluctuations. Investigation of strategies addressing stack and system thermal management for long-term operation.